2017
DOI: 10.18671/scifor.v45n113.14
|View full text |Cite
|
Sign up to set email alerts
|

Resistência biológica da madeira de espécies de eucalipto ao ataque de cupim de madeira seca

Abstract: ResumoA resistência ao ataque de cupins de madeira seca se constitui numa importante propriedade da madeira. Em se tratando das madeiras provenientes das espécies de Eucalyptus, tal atributo se torna ainda mais evidente, uma vez que essas madeiras são, na maioria das vezes, de difícil tratabilidade pelos métodos de convencionais. O objetivo do estudo foi determinar a resistência da madeira de sete espécies de eucalipto, ao ataque de cupim de madeira seca. AbstractThe resistance against dry wood termites is on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 6 publications
1
9
0
5
Order By: Relevance
“…The damage observed for impregnated samples was lower than that found by Oliveira et al (2017) for the wood of seven species of Eucalyptus coming from trees at 16 years, thus proving the improvement in the resistance of the impregnated samples, regardless of the oil and I 2 percentage used.…”
Section: /9mentioning
confidence: 58%
See 2 more Smart Citations
“…The damage observed for impregnated samples was lower than that found by Oliveira et al (2017) for the wood of seven species of Eucalyptus coming from trees at 16 years, thus proving the improvement in the resistance of the impregnated samples, regardless of the oil and I 2 percentage used.…”
Section: /9mentioning
confidence: 58%
“…wood, in addition to two holes in the samples of this wood being observed and termite mortality was 17.50%, which differed from other species such as Australian cedar, cacunda, cupiúba, cedar rose and pequi. Oliveira et al (2017) found severe damage (score 4) to Pinus sp. wood subjected to the same species of termites, with 15 holes and mortality of 34.4%, which was similar to that in the wood of seven Eucalyptus species at 16 years of age.…”
Section: /9mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it may present high, medium or low resistance to the action of these agents. It is one of the basic requirements that limits its use as sawn material (Oliveira et al, 2017), and the more marked it is, the greater its degree of acceptance in relation to the others (Oliveira et al, 2017), allowing its use without the need for toxic and environmentally harmful chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Curiously, resistance of tropical wood and its underlying causes were seldom investigated and the studies carried out so far focus on recognizing preferences and mainly by subterranean termite species with few exceptions (Cornelius & Osbrink, 2015;Lee, Bardunias, Su, & Yang, 2008;Lee & Forschler, 2016;Manzoor, Abbas, & Latif, 2015;Oberst, Lai, & Evans, 2018;Rust & Reierson, 1977;Rust & Su, 2012;Scheffrahn & Rust, 1983). Nonetheless, varied resistance to the West Indian drywood termite exists (Cosme, Haro, Guedes, Della Lucia, & Guedes, 2018;Gonçalves & Oliveira, 2006;Oliveira, Paes, & Vidaurre, 2017), and the wood physical properties, namely hardness and specially density, are important determinants of colonization and wood consumption by this invasive pest species (Cosme et al, 2018).…”
mentioning
confidence: 99%